INHERITANCE SYSTEM OF TINUTUAN GASTRONOMY IN MANADO CITY - Langi, Grace Kerly Lony (E-Journal of Cultural Studies; Volume 11, Number 1, February 2018DO - 10.24843/cs.2018.v11.i01.p04, 2018)
Tinutuan is known as a local culinary which is close to all socio-economic status, religion and belief, gender, and age. There is no limit to consuming it, therefore tinutuan can be accepted as one of the culinary choices for people outside the region and abroad. The problem now, things related to history, preparation, processing, and presentation tinutuan not all people Manado City find out tinutuan fans. This study aims to interpret the tinutuan gastronomic inheritance system so that tinutuan as gastronomy in Manado City is not marginalized even extinct. Research data in the form of observation, interview, literature study, and documentation by using qualitative approach. Informants were determined purposively. The results show formal and informal inheritance systems in gin tinutuan gastronomic practices. Tinutuan gastronomy became the culinary heritage of the city of Manado, therefore recommended inheritance system in the family and culinary business is not broken. In addition, the active role of society and educational organizations to socialize tinutuan culinary in the pattern of daily eating habits.